Pemetaan Prospek Pasar Wisatawan Nusantara di Indonesia - Maulana, Addin (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Utilizing the Tourism Potential Market Matrix (PPP) which is a modification of the Boston Consulting Group (BCG) Matrix, this study resulted in a mapping of the prospects of the domestic tourist market in Indonesia. From this study, it was identified the market potential that besides on the ability of a provinces to produce the number of trips for domestic tourists, and also has the potential of the prospect of spending while traveling. There are 5 Provinces which are included in the most potential market quadrant in the development of domestic tourist because they have a high average income, and the high on travel propensity, namely: Bangka Belitung Islands, DKI Jakarta, Riau Islands, North Sulawesi and DI Yogyakarta. These provinces can be optimized by other provinces to be developed as a tourism market, so that they are expected to bring quality tourists.